From one to many : scaling up health programs in low income countries - International Conference on Scaling Up Health Programs (2008 : Dhaka, Bangladesh); Cash, Richard A.; Chowdhury, A. M. Raza.; Smith, George B. (George Baxter), 1907-2003.; Ahmed, Faruque (Dhaka : The University Press Limited, 2011)
Contributed papers submitted to the International Conference on Scaling Up Health Programs, held in Dhaka, Bangladesh, in Dec. 2008.
First published.
Includes bibliographical references and index.
Keywords: Public health -- Developing countries -- Congresses